KUALITAS SUNGAI PETAPAHAN KECAMATAN GUNUNG TOARKABUPATEN KUANTAN SINGINGI - Helmi, Zafnil; Anita, Sofia (Jurnal Kajian Lingkungan, 2013)
Petapahan river, 6 Km long is one of river that is an administrative district in the region ofGunung Toar. This river has long been used for many activities by people who live along theriver. The study was conducted at the Petapahan River in November 2011. The aimof thisresearch is to determine the quality of the river in terms of parametersof Physics, Chemistryand Biology compared to pp.82 of 2011 on Water Quality Management and Air pollutionControl as well as to determine the appropriateallocationofriver waterqualityThe methodsusedin this study wasasurveymethodas PurposiveSampling. Eachstationintheobservationsetbasedon theenvironmental characteristics. Station1 is located at theup stream ofthePetapahan, Station 2 is in the middle of theRiver which are used for gold mining. Station3is a rural home,Station4 is in the down stream. Data were obtainedfromobservationsoftheprimarydataintermofPhysics,ChemistryandBiologyparameters.Physicalparametersoftheobservationsweretemperature, river’s flow,Total Suspended Solid (TSS) andchemicalparameterswere pH,Biological Oxygen Demand (BOD),Chemical Oxygen Demand (COD), Nitrate,PhosphateandBiologicalparameterswas makrozoobenthos. ThePetapahanRiveris catagorizedpollutedbeyondThresholdAirQuality StandardClass Iwhen it comparedto IndonesianPeraturan Pemerintah.82 2001andPetapahanRiverwater unfit toservetheneeds of thecommunity. It take sappropriatedesignationonlyasIrrigationWaterforPaddyCultivation.